A community-based approach to climate risk management: making insurance work for smallholders - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
CCAFS in South Asia is working with insurance companies and other stakeholders to help design innovative insurance products that are tailored to engage small-holder farmers in the management, reporting and veriﬁcation of insurance schemes. The community managed insurance scheme is one such novel idea.